2006
DOI: 10.1117/12.659593
|View full text |Cite
|
Sign up to set email alerts
|

Coupled transport/hyperelastic model for nastic materials

Abstract: Nastic materials are high energy density active materials that mimic processes used in the plant kingdom to produce large deformations through the conversion of chemical energy. These materials utilize the controlled transport of charge and fluid across a selectively-permeable membrane to achieve bulk deformation in a process referred to in the plant kingdom as nastic movements. The nastic material being developed consists of synthetic membranes containing biological ion pumps, ion channels, and ion exchangers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Generally, the system of nastic materials may consist of a BLM containing ion pumps, ion exchangers, ion cotransporters, and ion channels, as depicted in Figure 2. Homison and Weiland (2006) proposed a general model which can be used to predict the system response through the simultaneous solution of the governing equations for these transporters. In practical application, the explicit expression of the model needs the support of experimental data.…”
Section: Model Description Ion Transport Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the system of nastic materials may consist of a BLM containing ion pumps, ion exchangers, ion cotransporters, and ion channels, as depicted in Figure 2. Homison and Weiland (2006) proposed a general model which can be used to predict the system response through the simultaneous solution of the governing equations for these transporters. In practical application, the explicit expression of the model needs the support of experimental data.…”
Section: Model Description Ion Transport Modelmentioning
confidence: 99%
“…The fundamental model used in the current research can be found in the work given by Homison and Weiland (2006). (Sundaresan and Leo, 2006a).…”
Section: Model Description Ion Transport Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The need to understand the basic mechanisms of nastic actuation has previously been recognized (Homison and Weiland 2005). The modeling construct employed utilized the equations 2-7 through 2-20 from the previous discussion.…”
Section: Previous Mechanistic Nastic Modelmentioning
confidence: 99%